EHealth literacy among older adults living with cancer and their caregivers: A scoping review. Issue 5 (June 2022) - Verma, Ridhi; Saldanha, Conchita; Ellis, Ursula; Sattar, Schroder; Haase, Kristen R.
Abstract: Introduction: Over 90% of people living with cancer access information online to inform healthcare decisions. Older adults with cancer are also increasingly adopting electronic healthcare services, or eHealth, particularly with the rapid transition to virtual care amidst the pandemic. Therefore, the purpose of this review is to understand the level of eHealth literacy among older adults with cancer and their caregivers, as well as any barriers and facilitators in terms of accessing, comprehending, and implementing eHealth information. Methods: This scoping review was guided by Arksey and O'Malley methodology and PRISMA ScR guidelines. Comprehensive searches for the concepts of "eHealth Literacy" and "cancer" were performed in MEDLINE, Scopus, CINAHL, PsycINFO, AMED and EMBASE, from 2000 to 2021. We used descriptive quantitative and thematic analysis to analyze the literature. Results: Of the 6076 articles screened by two reviewers, eleven articles were included. Quantitative findings suggest older adults with cancer and their caregivers have low self-perceived eHealth literacy and less confidence evaluating online health information for cancer decision-making. Low socioeconomic status, lower education levels, rapid expansion of digital applications, broadband access, reduced familiarity, and frequency of use were cited as prominent barriers. eHealth literacy appears to be positively correlated with caregivers seeking a second opinion, awareness of treatment options, shared decision making, and trust in the health care system. Conclusion: With the growing reliance on eHealth tools, developing credible digital health applications that require minimal internet navigation skills, patient education, and collaborative efforts to address access and affordability are urgently warranted.